2021
DOI: 10.3892/etm.2021.9694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vibrant® Soundbridge™ positioning and results with laser doppler vibrometry and the finite element model

Abstract: The etiology of hearing loss originates from genetic factors and includes several other events including infections, working or living environment, as well as several endocrine and metabolic disorders. The Vibrant ® Soundbridge ™ (VSB) is an implantable hearing aid whose floating mass transducer (FMT) is attached to the long process of the incus. The device is used for pure sensorineural hearing loss with an intact middle ear. Variations in the manner of attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, the ratio of equivalent sound pressure is reduced when the excitation direction is 20° and 60° off the longitudinal axis of the stapes (84). Mocanu et al reported the same conclusion when the excitation direction was 45°-60° off the longitudinal stapes axis (85). Therefore, tilting of the actuator from the stapes longitudinal axis is likely to reduce hearing performance.…”
Section: Active Meimentioning
confidence: 92%
“…For example, the ratio of equivalent sound pressure is reduced when the excitation direction is 20° and 60° off the longitudinal axis of the stapes (84). Mocanu et al reported the same conclusion when the excitation direction was 45°-60° off the longitudinal stapes axis (85). Therefore, tilting of the actuator from the stapes longitudinal axis is likely to reduce hearing performance.…”
Section: Active Meimentioning
confidence: 92%
“…The conclusion of Due to the anatomic complexity, several mathematical models (static and dynamic behaviors) have been used to study ME function, all of them based on deterministic approaches [34][35][36][37][38]. Lumped element models, distributed parameter models, multi-body systems, and finite element models have been used to assess the function of the healthy ME [39,40], to evaluate pathological conditions [41], and also to verify results of ossicular chain reconstruction [42,43]. Because the high degree of variability among individuals leads to large discrepancies among samples, the ME behaves as an uncertain system, which means that stochastic models become very useful [34,44].…”
Section: Discussionmentioning
confidence: 99%
“…The finite element method is also widely used in the biomechanics of the middle ear (Kiryk et al, 2018;Gil Mun et al, 2019;Mocanu et al, 2021). This study developed a sound-structure coupling finite element model to evaluate the effectiveness of implanting vibrating materials into the tympanum.…”
Section: Figurementioning
confidence: 99%